The Construction Law System and Purification of Limitation from Bawaslu’s Authority - Mustakim Mustakim; Fradhana Putra Disantara (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
The aim of this research is analize Article 1 number 17 of Act No. 7 of 2017 concerning General Elections on the General Election Supervisory Agency (Bawaslu) as an election supervisory agency oriented towards monitoring the 'validity of the people's voice' and despite gaining strong legitimacy based on existing regulations. However, Bawaslu has several obstacles, including the issue of the enigma of Bawaslu's authority to give decisions related to the post-constitutional election decision from the Constitutional Court. This research methods was legal research using a conceptual approach and legislation based on three types of legal materials, namely primary legal materials, secondary legal materials, and non-legal materials. The results of this legal research show that when viewed from the aspect of structure, substance, and legal culture; the expansion of Bawaslu's authority has the potential to make Bawaslu less than optimal as well as to create overlapping powers between law enforcers; therefore, the aspects of professionalism and leadership must support it. In addition, the purification of the authority of Bawaslu is essential to optimize the duties and authorities of Bawaslu so that Bawaslu does not need to focus on expanding its authority.